Major Risk Factors for Gestational Glucose Intolerance and Gestational Diabetes Mellitus in Urban Areas of Jember - Wirapraja, Aristha Dwi; Marchianti, Ancah Caesarina Novi; Marufi, Isa (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Gestational Glucose Intolerance (GGI) and Gestational Diabetes Mellitus (GDM) is condition in which someone who leads to abnormally higher blood glucose levels. High glucose level on pregnant can influence mother itself and her fetus if it doesnât get prevention and right treatment. The purpose of this research was to know modified risk factors related with incidence of GGI and GDM in urban areas of Jember. This research was observational with cross sectional approach. Non probability sampling using purposive sampling was used in this research as sampling technique. Data were collected by interview and questionnaire that was distributed for 96 pregnant women who have been checked their blood glucose level in urban areas of Jember. The result of this research showed that over weight (p value= 0.001, OR= 16.15), less physical activities (p value = 0.000, OR=4.91) and unhealthy diet (p value = 0.000 OR=5.3) have significant correlation with GGI and GDM, while less physical activity (p value = 0.000 OR=0.176) as major risks with incidence of GGI and GDM. Pregnant women should do physical activities, like doing light exercises in accordance with their condition are offset by keeping dietary habits, so the blood glucose level during pregnancy could be controlled. Keywords: GGI, GDM, High glucose level, Overweight, Less physical activities, Unhealthy diet